Spectroscopic Characterization, Electronic Structure Analysis, and DFT Investigation of C??H??N?O? - Kebiroglu, Mehmet Hanifi; Yılmaz, Mücahit (Niyazi BULUT, 2025)
In this study, the electronic properties of 2-(Tetrahydro-2H-pyran-4-ylmethoxy)-4-pyrimidinecarboxylic acid (THPMPCA, C??H??N?O?) were investigated using density functional theory (DFT) calculations with the LanL2MB basis set (0.625 eV). Spectroscopic methods including Ultraviolet-visible (UV-vis), Fourier Transform Infrared (FTIR), and Nuclear Magnetic Resonance (NMR) were employed to characterize the structural and electronic properties of THPMPCA. Detailed electronic structure analyses such as density of states (DOS), highest occupied molecular orbital (HOMO), and lowest unoccupied molecular orbital (LUMO) calculations were performed to elucidate the electronic transitions and stability of the molecule. The results revealed significant improvements in electronic properties, suggesting enhanced applicability of THPMPCA in electronic and medical fields. This comprehensive investigation provides insight into optimizing THPMPCA for future technological and pharmaceutical applications.
Keywords: Atomic; Molecular and Optical Physics (Other); Atomik; Moleküler ve Optik Fizik (Diğer)